Analisis Penggunaan Humor dalam Filem Werewolf - Danasaputra, Iim Rogayah; Wanodyatama, Nike Puspita; Greenetia, Greenetia (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2023)
The paper entitled Analysis of Humour used in Werewolf. This research aimed to find out types, functions, and meaning of humour usage in the film. The method used was deductive method and technique of collecting data consisted of browsing internet, literary study and film. The result shows that both of the film used the types, function and meaning of humour. The difference lies on the number of each category. For the types of humor in the film Werewolf, there are 60% satire and 40% self-deprecation. In terms of the functions of humor used in film, namely to entertain listeners so they have positive energy, joke to help people who are experiencing mental health problems, and make people around them feel comfortable because people who like humor are friendly and welcoming. For the humorous meaning of every utterance and action carried out, namely using connotative and denotative meaning, in the Werewolf film it was found that 69% contained connotative meaning and 31% denotative.